ELDERLY FRIENDLY GREEN OPEN SPACE IN YOGYAKARTA: POLICY EVALUATION & WELFARE IMPACT - Ayu Fitri Khasanah; Muhammad Eko Atmojo (INDONESIAN GOVERNANCE JOURNAL : KAJIAN POLITIK-PEMERINTAHAN, 2025)
Along with the increasing number of elderly population, Yogyakarta City faces challenges in fulfilling green open space (RTH) that is friendly for elderly welfare. This study aims to evaluate the Yogyakarta City Government's policy in providing and managing RTH to enchance the quality of life of the elderly. Using a qualitative descriptive approach, this study examines the effectiveness, efficiency, adequacy, equity, responsiveness, and relevance of the policy using William N. Dunn's policy evaluation theory as a framework. Data were gathered through interviews with the Environmental Service of Yogyakarta City. The findings of the study show that although the RTH policy has been regulated in regional and national regulations, its implementation still faces various challenges. Some of them are limited land, unequal distribution of RTH between regions, lack of elderly-friendly facilities, and minimal community participation in planning. In addition, constraints in budget management also hinder the optimization of RTH utilization. Therefore, a strategy is needed to increase accessibility, strengthen regulations, and actively involve the elderly in the planning process. With these steps, it is hoped that RTH in Yogyakarta City can be more inclusive and contribute to the welfare of the elderly.